From the Eye of the Gods to the Eye of Google? Ref lections on the Inf luence of Aerial Photography on Architectural Design (diségno, 2023)
The representation and communication of contemporary architecture is going through a moment of paradigm shift in which the presence and use of photography is becoming increasingly prominent both when it comes to images of the actual building and when the image is synthetically generated from a three-dimensional mode. Already during the first modern movement we thought of buildings seen from above, from a biplane flight, and even earlier the bird’s eye perspective showed how on some occasions the compositional effort was concentrated on a part of the building that would never be seen directly, but only perceived through its representation. Nowadays, aerial photography is gaining increasing importance both in communication and in the conception of the architectural project thanks to the existence of satellite applications, which mediate our perception of it to the point that it is possible to argue that the roof has transformed into fifth facade of the building and that this is, at times, the most important one. In this contribution we present a reflection on the importance that the point of view from above has acquired in the photographic narrative of architecture. Proposing an analysis of the various circumstances that have propitiated it such as: the digital use of architecture, the massive use of systems that favor the aerial view of the city and finally the expansion of the possibilities of aerial photography using drones and other devices.
Keywords: aerial photography; contemporary architecture; Google Maps; drones